The illustrated a brief history of time - Hawking, S. W. (Stephen W.); Hawking, S. W., (Stephen W.) (New York : Bantam Books, 1996)
Provides an introduction to today's scientific ideas about the cosmos and reviews past theories. Also covers black holes, quarks, antimatter, and other mysteries of physics.
Includes index.
Books for the Teen Age (NYPL).
Young Adult
Keywords: Cosmology; Physics; Universe; Cosmology; Physics; Universe